2016
DOI: 10.4103/0973-1296.182177
|View full text |Cite
|
Sign up to set email alerts
|

Ketosteroid standardized Cissus quadrangularis L. extract and its anabolic activity: Time to look beyond ketosteroid?

Abstract: Background:Cissus quadrangularis (CQ) L. reported to contain 3-ketosteroids and have bone health benefits.Aim:This study aimed at establishing the relationship between the ketosteroid content and anabolic as well as bone health-promoting activities of various Cissus extracts in well-established orchidectomized (ORX) rat model.Materials and Methods:Supercritical carbon dioxide, ethyl acetate, and aqueous extracts (AE) of CQ L. were prepared and standardized for ketosteroid content by two methods used in commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Ketosteroid content, which is currently used for the standardization of CQ supplements in USA, was not correlated with the plant effect on the bone parameters (mean bone density, strength, and calcium content) in an animal model of osteoporosis (Jadhav et al, 2016).…”
Section: Active Phytochemicalsmentioning
confidence: 91%
See 1 more Smart Citation
“…Ketosteroid content, which is currently used for the standardization of CQ supplements in USA, was not correlated with the plant effect on the bone parameters (mean bone density, strength, and calcium content) in an animal model of osteoporosis (Jadhav et al, 2016).…”
Section: Active Phytochemicalsmentioning
confidence: 91%
“…Several studies showed the capacity of CQ to reduce bone loss, as evidenced by the bone weight gain, density, strength, and calcium content in ovariectomised or orchidectomized animals (Jadhav et al, 2016;Potu et al, 2009). Maternal administration of CQ extract during pregnancy stimulated the development of fetal bone growth during the intra-uterine period in rats (Potu et al, 2008).…”
Section: Animal Studiesmentioning
confidence: 99%
“…The plant is a significant medicinal herb due to its numerous therapeutic properties and diversified uses stated above. The talk that follows goes into great detail into pharmacological activity [14][15][16][17][18].…”
Section: Pharmacological Profilementioning
confidence: 99%
“…Quercetin from CQ causes its toxic effects on breast cancer, colon cancer, ovarian carcinoma, and leukaemia cells, according to in vitro and in vivo research. According to toxicological studies, the CQ extract has no harmful toxic effects 24,9,20 . Numerous molecules possessing anti-tumour characteristics have been isolated from CQ and examined for its anticancer properties in human glioblastoma U87 MG cells.…”
Section: Cq Against Brain Cancermentioning
confidence: 99%